Community Policing in Nigeria: Rationale, Principles, and Practice - Onyeozili, Emmanuel; Agozino, Biko; Agu, Augustine; Ibe, Patrick (Virginia Tech Publishing, 2021)
One result of the Black Lives Matter movement has been to focus attention on police brutality in all its forms around the globe. Nowhere is the situation more dire than in Nigeria where the now infamous SARS (Special Anti-Robbery Squads) have, for years, inflicted excessive abuses on Nigeria’s citizenry. In response, many young people have taken to the streets to demand an end to the brutality in the now historic #ENDSARS nationwide protest. Community Policing in Nigeria is a timely and much-needed intervention into the policing problems in Nigeria. Written collaboratively by four authors with deep knowledge of Nigerian policy and of criminal justice more broadly, the book examines models of community policing around the world and points out best practices and flawed practices that may serve as guides for Nigeria and the rest of Africa. Community Policing in Nigeria is published in the United States by Virginia Tech Publishing and in Nigeria by Fourth Dimension Publishing.